The influence of Î±-Naphtaleneacetic Acid (NAA) on somatic embryogenesis moon orchid Phalaenopsis amabilis (L.) Bl. - EDY SETITI WIDA UTAMI; ISSIREP SUMARDI; TARYONO TARYONO; ENDANG SEMIARTI (Society for Indonesian Biodiversity, 2007)
An experiment to analyze the effect of plant growth regulator Î±-Naphtaleneacetic Acid (NAA) on somatic embryogenesis moon orchid Ph amabilis (L.) Bl. was carried out. One year old of plantlets were used as explants sources. Basal leaf of these explants were cultured in medium New Phalaenopsis (NP) added with 0,1 mg/L, 1 mg/L, 2 mg/L, 3 mg/L, and 4 mg/L NAA. The explants were cultured in medium NP without NAA were used as control. The formation of embryogenic callus was observed every day, while the formation of somatic embryo was observed every week for 6 week using a dissecting microscope. The result showed that somatic embryogenesis Ph amabilis (L.) Bl were influenced by plant growth regulator NAA. Explants were cultured in medium NP without NAA didnâ€™t embryo formed, while explantswere cultured in medium NP added with 2 mg/L, 3 mg/L, and 4 mg/L NAA embryo formed at embryogenic callus appear. These somatic embryos formed as an indirect via callus phase.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: moon orchid, Î±-Naphtaleneacetic Acid (NAA), somatic embryogenesis